PENGARUH PENERAPAN MEDIA SOFT BOOK TERHADAP KEMAMPUAN MENGENAL HURUF HIJAIYAH PADA ANAK USIA 5-6 TAHUN PAUD AL-IKHWAN DESA SERI BANDUNG OGAN ILIR - Suci, Suci; Handayani, Tutut; Putra, Yecha Febrieanitha (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to determine the Effect of the Application of Soft Book Media on the Introduction of Hijaiyah Letters. This type of research is quantitative with the experimental research method Pre-Experimental Design. The design of this research is One Group Pre-test Post-test Design. The population of this study were children in groups A - B2 totaling 75 children. The sample used was in class B2 totaling 24 children. Data collection techniques used observation, documentation, and testing techniques. Data analysis techniques in this study used validity tests, reliability tests, normality tests, homogeneity tests, and t-test hypothesis tests. Based on the results obtained that there is an influence of the average value after the implementation of treatment activities using gamolan musical instruments where the average pre-test value before being given treatment is 79.01 and the average post-test after being given treatment is 328.7. Then based on the calculation of t where the t table value for 5% significance is 2.178 it can be concluded that the t count value> t table (26.741> 2.178) then Ho is rejected and Ha is accepted, so it can be concluded that the Soft book media has an influence on the ability to recognize the hijaiyah letters.